Realization of Swear Word in Reynhard Sinaga’s Case on ‘Twitter’ - Zhana Sabrina Amelia; Eddy Setia; Umar Mono (PT FORMOSA CENDEKIA GLOBAL, 2022)
The research found how the realization of swear word in RS’s case in twitter. By analysed the tweet to know how the realization of use swear word trough the motive has used to find out the reasons use swear words related to the RS’ case. The motive has found how to realization swear word in RS’s case are psychological motive, social motive and linguistic motive. Supporting research by analysed the tweets related in RS’s case, as many 121 clauses were obtained. It found psychological motive is the most motive has used by twitter’s users.